Educación, accesibilidad y discapacidad: hacia un diseño justo e inclusivo del derecho humano a la educación superior de las personas con discapacidad en Latinoamérica - Robledo, Diego (Teatro, 2022)
A reflection is carried out on higher education and the human rights of people with disabilities to build an educational design based on inclusion, justice and accessibility. Disability cuts across people’s lives and can be compounded by other vulnerabilities. Starting from the Convention on the Rights of Persons with Disabilities and the Inter- American Convention for the elimination of all forms of discrimination against persons with disabilities, we think of human rights in movement and action. From the materiality of the bodies, different ways of perceiving people with disabilities are focused: model of disregard, rehabilitative medical model, social model of disability, functional diversity and critical disability. They are embedded in culture and it is necessary to be aware that educational inclusion requires revaluing people, equal in dignity and rights. Assume diversity and become aware of the physical or environmental, cultural, cognitive, technological, and attitudinal barriers that exist in educational practices and that need to be transformed. We act for an inclusive educational design and project of higher education for people with disabilities that prevents, transforms, includes, pacifies-restores, and emancipates society.